Arab Intellectuals and the Bush Administration's Campaign for Democracy - Baroudi, Sami E. (2007)
This article considers how Arab intellectuals represent the United States and American foreign policy in their editorial contributions to Arabic newspapers. As a case study, it examines Arab intellectuals' reactions to the George W Bush Administration's campaign to effect democratic change in the Middle East, as articulated in the Administration's 2004 Greater Middle East Initiative (hereafter GMEl or Initiative). I argue that the predominantly hostile reactions to the GMEI stemmed mainly from a closed and negative image of the United States permeating Arab intellectual circles. This negative image is the product of the history of American policy towards the region and, equally important, of the beliefs, values, and formative experiences of Arab intellectuals. The article concludes by addressing ways to ameliorate this image